Irradiation of intraerythrocytic Plasmodium berghei with a fractionated dose of gamma rays does not effectively reduce the infectivity in mice Mus musculus - Mukh Syaifudin; Siti Nurhayati; Darlina Darlina; Yanti Lusiyanti; Teja Kisnanto (Aceh Journal of Animal Science, 2019)
Malaria infection kills more than one million human every year, mainly under-5-year-old children, including in South East Asian nations. Gamma radiation given at a single dose is commonly used to create the attenuated Plasmodium parasites to get vaccine materials. However, there is no study on the infectivity of parasites after fractionated γ-radiation. This study aimed to assess the infectivity of parasites after irradiated with fractionated γ-rays in mice. A number of Plasmodium bergheithat was irradiated in two fractions of 100 and 50 Gy, 100 and 75 Gy; and 100 and 100 Gy within 5 minutes of interval time was injected intraperitoneally into 12 mice. Mice injected with unirradiated parasites (0 Gy) served as a control group. The parasitemia level of intraerythrocytic parasites in each group was observed at days post injection up to 20 days by making Giemsa stained thin blood smears and observed under the microscope. Results showed that fractionation radiation did not effectively attenuate the parasites where they still grew in blood of mice, except for 100+75 Gy. There are no significant differences among the treatment groups (p0.05). This is different from irradiation at the single dose that resulted in almost completely attenuated parasites mainly the dose of 150 Gy. This implicating that irradiation of gamma rays at a single dose is a better way to mitigate parasites than fractionation dose as the infectivity of irradiated parasites were lower compared to that of fractionated dosage. Keywords: Malaria vaccine, Gamma radiation, Fractionation, Parasitemia